Analisis Sektor Unggulan Kabupaten Dharmasraya - Rovi Thamrin; Menik Kurnia Siwi (Universitas Negeri Padang, 2020)
The purpose of this research is to analyze the excellent sector in Dharmasraya District and analyze the development strategy of the top sector in Dharmasaraya district. The study used secondary data using 17 research sectors in Dharmasraya District, during the year 2014-2018. Data analysis techniques are used to analyse superior sectors and analyze strategies to develop superior sectors using the Location Quotient (LQ) and Shift share analytical techniques. As for data processing using Microsoft Excel. Based on LQ and Shift Share calculations to classify commodities, the superior sector in Dharmasraya District is agriculture, forestry and fisheries, construction, information and communication, real estate, government administration, and social security, physical and social activities.Keywords : leading sector, LQ, shift share